Using Administrative Data to Evaluate Municipal Reforms : An Evaluation of the Impact of Minas Fácil Expresso - Bruhn, Miriam; McKenzie, David (Taylor and Francis, 2013)
This study uses administrative data to evaluate the impact of Minas Fácil Expresso, a programme in the State of Minas Gerais, Brazil, which expanded a business start-up simplification programme to more remote municipalities. Using difference-in-differences with 56 months of registration data for 822 municipalities, the analysis finds introducing the programme actually led to a reduction in registration rates, and no change in tax revenues. The paper uses this evaluation to illustrate the design choices and the issues involved in using administrative data to evaluate reforms, also providing a template that can be used for evaluating similar reforms elsewhere.